Resilience in Women with Dual Roles Who Have Ngayah Responsibilities in Balinese Culture - Vania Sharira Hyacintha Prabaswari Mahadhini; Diana Rahmasari (SAINTIS Publishing, 2026)
Balinese women have complex dual roles, encompassing domestic responsibilities, productive roles, and the cultural obligation of Ngayah within customary structures. This situation has the potential to create role conflict, particularly when the time and energy demands of these various roles clash. This study aims to understand the dynamics of dual role conflict and resilience among Balinese women who carry out Ngayah responsibilities. The study used a qualitative approach using in-depth interviews with married, employed, and traditional Balinese women. Data were analyzed using thematic analysis and triangulation to identify patterns of participants' experiences, meanings, and adaptation strategies. The results indicate that dual role conflict primarily arises from difficulties managing time between customary obligations, work, and family responsibilities. Nevertheless, Balinese women demonstrate strong resilience through various strategies, such as using a priority scale, scheduling customary activities, managing emotions through enjoyable activities, and receiving support from the nuclear family and traditional community. Ngayah is interpreted as an obligation carried out sincerely and becomes a source of spiritual meaning, thus strengthening women's resilience in facing role pressures. Resilience is also formed through cultural values instilled from an early age by the family. This research emphasizes the importance of understanding women's resilience in the context of local culture as an effort to enrich the study of cultural and gender psychology.